Main aspects of educational interventions for children with autism spectrum disorders - Lamiya Panah Ahmadli-Shironova (Modern Scientific Technology, 2024)
About 70 million people, which is 1% of the world's population, are known to have autism. According to a study conducted in the United States of America in recent years, one out of every 59 children has symptoms of autism. In general, on average, one in every 68 children is known to suffer from this spectrum disorder. Currently, there are more than 10 million autistic individuals worldwide. Autism Spectrum Disorder is 4 times more common in boys than in girls. Autism is one of the reasons for the increase in disability among children. Currently, there are no official statistics on the number of individuals with autism in our country. In many cases, for various reasons, families hide these violations or they do not have enough information about this problem. In some cases, individuals with autism are registered under different names. According to the statistical research conducted by non-governmental organizations, it is known that there are about 6,000 autistic individuals in our country (https://www.autizmportali.az/). Children with autism who receive an early diagnosis have the opportunity to be involved in rehabilitation programs sooner. In addition, the knowledge and skills that children learn in the first five years have an important impact on their future development. At this age, the support children with autism receive is more continuous. In general, it is also known that the learning of some skills is related to the age period. At a younger age, autistic children respond positively to support in the field of language development, but at advanced ages it is observed that this is not possible. Behavioral and other problems are permanently formed in autistic children who do not receive rehabilitation and various educational support at an early age, and it becomes difficult to get results from the programs provided. With support programs initiated as a result of early diagnosis, the possibility of eliminating behavioral disorders in children with autism is much higher.